Leech‐Inspired Shape‐Encodable Liquid Metal Robots for Reconfigurable Circuit Welding and Transient Electronics. (7th July 2022) - Wang, Ben; Zhang, Baofeng; Tan, Yongzhu; Ji, Fengtong; Lv, Guanghui; Pan, Chengfeng; Handschuh-Wang, Stephan; Zhang, Li; Zhou, Xuechang
Abstract : Deformability and self‐adaptability are important for soft robots to deal with uncertain and varying situations and environments during movement and navigation. Droplet‐based robots are great candidates to travel inside narrow and constrained spaces without damaging the interfaces due to their extreme deformability and liquid nature, which enables smooth contact between robots and target spaces. Here, magnetic liquid metal droplet robots, comprising liquid metal and carbonyl iron, that can perform reversible telescopic deformation, bending, and on‐demand locomotion are proposed. The magnetic liquid‐metal‐based robots can perform on‐demand and reversible coalescence and splitting by intricately applying magnetic fields. Importantly, the liquid metal robot can perform phase transition to fix the desired shape after programmable shape encoding. The liquid‐metal‐based soft robots can serve as dynamic and recyclable switches for complex circuits, and are capable of repairing damaged sections of microcircuits by remote actuation, controllable coalescence, and on‐demand circuit welding. This technology provides a new application scenario of droplet‐based soft robots for on‐demand circuit welding and transient recyclable electronics. A preprint version of the article can be found at: https://www.authorea.com/doi/full/10.22541/au.165167005.56125584. Abstract : Liquid‐metal‐based soft robots serve as dynamic and recyclable switches for complex circuits, and are capable of repairing damaged sections of microcircuits by remote actuation, controllable coalescence, and on‐demand welding.